Analisis Penerapan Model Problem Based Learning (Pbl) dengan Media Wordwall Pada Mata Pelajaran IPAS Kelas V SDN Mlatiharjo 02 - Puspitasari, Cindy; Reffiane, Fine; Darminingsih, Anik; Setyawati, Rina Dwi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to analyze the application of the Problem Based Learning (PBL) model with Wordwall media in fifth grade Natural and Social Sciences subjects at SDN Mlatiharjo 02. This research is qualitative research with a descriptive approach. Data collection was carried out through observation, interviews and documentation. Data analysis uses an interactive model which includes data reduction, data presentation, and drawing conclusions. The results of research conducted on 26 fifth grade students showed that the implementation of the PBL model with Wordwall media in fifth grade natural and social science subjects at SDN Mlatiharjo 02 had been implemented well. The teacher has implemented the stages of the PBL model, namely orienting students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting work results, and analyzing and evaluating the problem solving process. Wordwall media has also been used effectively to visualize problems, present questions, and help students understand learning material. The application of the PBL model with Wordwall media can increase student activity and learning outcomes in fifth grade natural and social science subjects at SDN Mlatiharjo 02.